Examining missing pieces of the human resource (HR) attributions puzzle: The interplay between line manager beliefs, HR information and context - Vuorenmaa, Hertta; Sumelius, Jennie; Sanders, Karin (Frontiers in Psychology, 2023)
While previous research acknowledges the importance of line manager interpretations of information coming from the HR department for explaining various employee attitudes and behaviors, less is known about the antecedents of these interpretations, also known as HR attributions. This paper provides a qualitative examination of the interplay between three key antecedents of HR attributions, namely line manager beliefs about the HR department, information from the HR department and context. Our analysis is based on 30 interviews with HR professionals and line managers in three units of one organization. Our findings suggest that differences in context have a strong impact on line manager beliefs about HR, influencing the way line managers see HR practices, processes and the role of the HR department, and consequently the way they interpret information coming from HR. Our analysis extends our understanding of the variability in line manager interpretations of HR information. Our results contribute to existing research on HRM strength and HR attributions by highlighting the importance of focusing not only on the consistency of the HR system, but also on individual line managers beliefs about HR, and the context in which HR processes take place.